Late physical effects of childhood cancer survivors - Young-Ho Lee (Korean Pediatric Society, 2010)
Advances in research and medical and supportive care have contributed to a growing population of adults formerly treated for childhood cancer. History of cancer and its therapy can have significant life-long health implications. Late effects of cancer therapy can be insidious on onset, occur outside the pediatric age, and contribute to premature morbidity and mortality. In this review, I have focused on the key long-term effects of pediatric cancer therapy, particularly on the metabolic syndrome, including cardiopulmonary complications, infertility, and secondary neoplasm.